1994
DOI: 10.1152/ajprenal.1994.266.6.f868
|View full text |Cite
|
Sign up to set email alerts
|

H(+)-ATPases of renal cortical and medullary endosomes are differentially sensitive to Sch-28080 and omeprazole

Abstract: Adenosinetriphosphatase (ATPase) activity stimulated by K+ and inhibited by Sch-28080 (SCH), omeprazole (OME), and vanadate has been measured in microsomes from mammalian renal medulla and attributed to a kidney isoform of the H(+)-K(+)-ATPase. To determine whether the H(+)-K(+)-ATPase inhibitors could also inhibit the vacuolar (V)-type H(+)-adenosinetriphosphatase (H(+)-ATPase, i.e., H+ pump) in mammalian intracellular vesicles, we examined their effects on bafilomycin-sensitive acidification in renal cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 0 publications
2
46
0
Order By: Relevance
“…ECL cells accumulate acridine orange [acidic dissociation constant (pK a) ϳ 9.0] in their histamine-containing vesicles due to the acidic pH of 5-5.5 generated by the activity of a V-type ATPase that is insensitive to inhibition by SCH28080 at concentrations Ͻ100 M (44). At this pH and dye concentration, the ECL cell histaminecontaining vacuoles show combined red and green fluorescent emission resulting in a yellow fluorescent appearance of ECL cells at an excitation wavelength of 488 nm.…”
Section: Fluorescence-assisted Cell Sortingmentioning
confidence: 99%
“…ECL cells accumulate acridine orange [acidic dissociation constant (pK a) ϳ 9.0] in their histamine-containing vesicles due to the acidic pH of 5-5.5 generated by the activity of a V-type ATPase that is insensitive to inhibition by SCH28080 at concentrations Ͻ100 M (44). At this pH and dye concentration, the ECL cell histaminecontaining vacuoles show combined red and green fluorescent emission resulting in a yellow fluorescent appearance of ECL cells at an excitation wavelength of 488 nm.…”
Section: Fluorescence-assisted Cell Sortingmentioning
confidence: 99%
“…We therefore investigated whether lysosomal enzymes playa role in OM-induced apoptosis. A number of studies have evidenced the lysosomotropic properties of OM and have indicated that following activation by protonation, it can also affect the activity of proton pumps, such as the vacuolar H+-ATPase (5,6,8,49) in part responsible for the internal acid milieu of! ysosomes (9-10).…”
Section: Fl3mentioning
confidence: 99%
“…They act as potent inhibitors of the gastric acid pump and have been used for short-or long-term treatments also with very high doses (150 mg/d) without major side effects (19,20). Besides targeting the gastric acid pump, PPI inhibit the V-ATPase activity (21)(22)(23). We reported that PPI sensitize chemoresistant human tumors to cytotoxic drugs (24), suggesting that proton pump activity may affect cancer cells homeostasis and particularly acidic vesicles trafficking (5,24).…”
Section: Introductionmentioning
confidence: 99%